2014
DOI: 10.3389/fpls.2014.00301
|View full text |Cite
|
Sign up to set email alerts
|

Functions of autophagy in plant carbon and nitrogen metabolism

Abstract: Carbon and nitrogen are essential components for plant growth. Although models of plant carbon and nitrogen metabolisms have long been established, certain gaps remain unfilled, such as how plants are able to maintain a flexible nocturnal starch turnover capacity over various light cycles, or how nitrogen remobilization is achieved during the reproductive growth stage. Recent advances in plant autophagy have shed light on such questions. Not only does autophagy contribute to starch degradation at night, but it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 57 publications
(85 reference statements)
0
34
0
Order By: Relevance
“…However, plants activate autophagy during various stress responses (such as starvation, pathogen infection, and oxidative stress) and developmental transition (for example, germination, flowering, or senescence; Lv et al, 2014;Marshall and Vierstra, 2018). While a function of autophagy in nutrient recycling under C, N, or S starvation has been established (Li and Vierstra, 2012;Avila-Ospina et al, 2014;Ren et al, 2014;Dong et al, 2017b), its role during Pi deficiency has received little attention. Only a few studies in yeast, algae, and tobacco BY-2 cells have reported induction of autophagy upon Pi deprivation, although to a much lesser extent than under N starvation, a result explained by the high capacity of vacuoles to store Pi or polyphosphates (Tasaki et al, 2014;Shemi et al, 2016;Yokota et al, 2017;Avin-Wittenberg et al, 2018;Couso et al, 2018).…”
mentioning
confidence: 99%
“…However, plants activate autophagy during various stress responses (such as starvation, pathogen infection, and oxidative stress) and developmental transition (for example, germination, flowering, or senescence; Lv et al, 2014;Marshall and Vierstra, 2018). While a function of autophagy in nutrient recycling under C, N, or S starvation has been established (Li and Vierstra, 2012;Avila-Ospina et al, 2014;Ren et al, 2014;Dong et al, 2017b), its role during Pi deficiency has received little attention. Only a few studies in yeast, algae, and tobacco BY-2 cells have reported induction of autophagy upon Pi deprivation, although to a much lesser extent than under N starvation, a result explained by the high capacity of vacuoles to store Pi or polyphosphates (Tasaki et al, 2014;Shemi et al, 2016;Yokota et al, 2017;Avin-Wittenberg et al, 2018;Couso et al, 2018).…”
mentioning
confidence: 99%
“…Specifically, four transcripts for three putative different isoforms of autophagy‐related protein 8 resulted significantly downregulated ( Autophagy‐related protein 8 g , Autophagy‐related protein 8e , Autophagy‐related protein 8f ) (Table and ). The possible involvement of certain ATG genes in plant carbon metabolism and signalling has been recently suggested, and ATG8e in particular belongs to a core carbon signalling response shared by a large number of Arabidopsis accessions (Ren, Liu, & Gong, ; Sulpice et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last five years, reviews have been published for plastid peptidases (Nishimura et al, 2016(Nishimura et al, , 2017, mitochondrial peptidases (Janska et al, 2010;Kwasniak et al, 2012;Mossmann et al, 2012), degradation of photosystem II (Chi et al, 2012;Yoshioka-Nishimura and Yamamoto, 2014), and specific peptidase families in plant organelles, including rhomboids and other intramembrane cleaving peptidases (Knopf and Adam, 2012;Adam, 2013;Jeyaraju et al, 2013), CLP (Nishimura and van Wijk, 2015), LON (Rigas et al, 2012(Rigas et al, , 2014, DEG , FTSH (Liu et al, 2010;Wagner et al, 2012), and processing peptidases (Teixeira and Glaser, 2013). Recent reviews on biogenesis of plastids (Jarvis and López-Juez, 2013;Ling and Jarvis, 2015), mitochondria (Carrie et al, 2013;Welchen et al, 2014) and peroxisomes (Hu et al, 2012), and autophagy of plant organelles (Li and Vierstra, 2012;Ishida et al, 2014;Lee et al, 2014;Ren et al, 2014;Van Aken and Van Breusegem, 2015) and protein turnover in plants (Nelson and Millar, 2015) complement these reviews on organelle proteolysis. A universal classification system for peptidases, as well as proteinaceous peptidase inhibitors, has been developed in which each protein is assigned to a family on the basis of statistically significant similarities in amino acid sequence (Rawlings et al, 2016).…”
Section: Introductionmentioning
confidence: 99%